How we approach malignant infantile osteopetrosis. Issue 3 (12th December 2020) - Even‐Or, Ehud; Stepensky, Polina
Abstract: Malignant infantile osteopetrosis (MIOP) is a rare hereditary disorder characterized by excessive bone overgrowth due to a defect in bone marrow resorption by osteoclasts. In most cases, hematopoietic stem cell transplantation (HSCT) may correct bone metabolism but the rapidly progressing nature of this condition necessitates early diagnosis and prompt treatment to minimize irreversible cranial nerve damage. The management of patients with MIOP presents many unique challenges. In this review, the clinical management of patients with MIOP is discussed, including diagnosis, preparation for HSCT and special transplant considerations, management of unique HSCT complications, and long‐term follow‐up.